1982
DOI: 10.1128/iai.37.3.975-980.1982
|View full text |Cite
|
Sign up to set email alerts
|

Production of a fecal mutagen by Bacteroides spp

Abstract: Forty species of anaerobes were screened for the ability to produce an etherextractable mutagen which is present in the feces of 15 to 20% of individuals in populations at high risk for colon cancer. This mutagen can be produced in vitro by incubating the feces of these individuals anaerobically or by supplementing anaerobic broths with methanol extracts of the feces and incubating them with a dilute fecal inoculum. Of the anaerobes screened, strains of five species of Bacteroides (B. thetaiotaomicron, B. frag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

1983
1983
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…In vitro, the Bacteroides spp. are incapable of producing fecapentaenes unless provided with these precursors, usually in the form of a methanol extract of feces of an individual who excretes fecapentaenes (19,20). The origin of these precursors is unknown.…”
Section: Lipids 24 454-459 (1989)mentioning
confidence: 99%
“…In vitro, the Bacteroides spp. are incapable of producing fecapentaenes unless provided with these precursors, usually in the form of a methanol extract of feces of an individual who excretes fecapentaenes (19,20). The origin of these precursors is unknown.…”
Section: Lipids 24 454-459 (1989)mentioning
confidence: 99%
“…The DNA hybridization assay used for identifying Bacteroides species in this study is simpler and more accurate than the conventional procedures (9). The 10 species of Bacteroides used for DNA probes are the predominant species found in human feces (6,9), and some of these species may play a role in inducing colon cancer through the production of fecapentaenes or other mutagens (14). These pilot data therefore justify the use of colonoscopy aspirates from patients prepared with a polyethylene glycol-electrolyte lavage solution for accurately measuring individual colonic microflora.…”
mentioning
confidence: 96%
“…Although it has been postulated that intestinal microflora plays a role in the etiology of large-bowel cancer, the exact mechanisms remain unclear. Limited in vitro studies have identified mutagen-producing bacteria in an Ames assay (12,14). However, conflicting results exist with regard to the association of specific bacterial species and colon cancer.…”
mentioning
confidence: 99%
“…As a first step of our study, we describe here the usefulness of a bacterial DNA hybridization assay for identifying intestinal Bacteroides species. Some Bacteroides species are thought to play a role in inducing colon cancer through production of fecapentaenes, mutagens found in human feces (26). Our final goal is to investigate the possibility of identifying persons that are at high risk for colorectal neoplasia on the basis of their fecal bacterial profile and are thus suitable targets for cancer screening and other preventive measures.…”
mentioning
confidence: 99%